Attention-deficit Disorder, Family Factors, and Oral Health Literacy - Mirella de Fátima Liberato de Moura; Ramon Targino Firmino; Érick Tássio Barbosa Neves; Edja Maria Melo de Brito Costa; Saul Martins Paiva; Fernanda Morais Ferreira; Ana Flávia Granville-Garcia (Elsevier, 2022)
ABSTRACT: Introduction: Relationships amongst attention-deficit/hyperactivity disorder (ADHD), family factors, and oral health literacy (OHL) in adolescents are unclear. The objective of this research was to investigate whether family environment and signs of ADHD are associated with OHL at the onset of adolescence. Methods: A cross-sectional study was performed with 448 twelve-year-old adolescents enrolled in schools in Cajazeiras, Brazil. Adolescents responded to an instrument measuring OHL (Brazilian version of the Rapid Estimate of Adult Literacy in Dentistry [BREALD-30]) and a validated questionnaire addressing family cohesion and adaptability (Family Adaptability and Cohesion Scales [FACES III]). Parents and teachers answered subscales of the Swanson, Nolan, and Pelham Questionnaire (SNAP-IV) and a socioeconomic questionnaire. Adjusted Poisson regression analysis was employed for the data analysis (P < .05). Results: Greater OHL was found in adolescents with higher family cohesion scores (rate ratio [RR], 1.02; 95% confidence interval [CI], 1.01-1.03), those whose mothers had more than 8 years of schooling (RR, 1.07; 95% CI, 1.03-1.12), and those whose families earned more than the Brazilian minimum salary (RR, 1.08; 95% CI, 1.03-1.12). Higher family adaptability scores (RR, 0.99; 95% CI, 0.98-0.99) and more signs of ADHD (teachers' reports) (RR, 0.95; 95% CI, 0.91-0.99) were associated with lower OHL. Conclusions: OHL in adolescents was influenced by family adaptability and cohesion, signs of ADHD, maternal schooling, and family income.